Fighting Against Corruption (A Political Biography of ‘Umar Ibn ‘Abd al-‘Aziz) - M. Abdul Karim (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2007)
Umar ibn Abd Aziz was a great leader throughout Islamic history. He has shown an outstanding role in the Umayyad Dynasty. He differed from some of his corrupt, unkind and injustice predecessors. This Caliph, well-known as Umar II, usually made popular policies to his people. He is the legendary leader who has many interesting historical evidences that encourage researchers to make further studies. His policies were always based upon Al-Qur’an and Hadits. On the one hand, he led and treated his people with justice; and on the other, he was very strict to his officials or people who corrupt or violate Allah’s rules. This study reveals various political decisions that were made during his leadership. Based on the various sources, many political decisions that he made may become references to be followed by Moslem leaders today and in the future time.Keywords: Economic policy, government system, social welfare, and justice